The relationship between selected employee benefits and organizational attractiveness - Tan Yen, Yee (Universiti Malaysia Sarawak (UNIMAS), 2019)
The purpose of this study is to investigate the relationship between selected employee benefits and organizational attractiveness in one of the financial institution at East Malaysia. The independent variables of this study include the flexible working hour, wellness program and medical benefits while the dependent variable of this study is organizational attractiveness. This is a correlational quantitative study where Spearman Rank - Order Correlation Coefficient and Multiple Regression were used to design this study. Pilot test was first conducted with 30 respondents to analyse the validity and reliability of the instruments using Cronbach's Alpha. Another 80 respondents then participated in actual data collection. This study was conducted using non-probability sampling technique, convenience sampling. Close - ended questionnaires with 5- point Likert Scale were used as study's instrument. Software Package for Social Sciences (SPSS) 23.0 was used to conduct descriptive statistics and inferential statistics data analysis for this study. The study showed that all of the selected employee benefits have significant positive relationship with organizational attractiveness. Wellness program is the dominant factor among the selected employee benefits in this study. This study hence brings implication and contributions to body of knowledge in organizational attractiveness, organizations' policy and HR practitioners. Future research may be conducted with different employee benefits or different research methodology like qualitative research. Not only that, this study also may be conducted in different industry or sectors including public sector or private sector.